No hard feelings [videorecording (DVD)] - Stupnitsky, Gene; Phillips, John M. (John Masterson); Lawrence, Jennifer, 1990-; Feldman, Andrew Barth; Benanti, Laura; Morales, Natalie; Broderick, Matthew, 1962- (Sony Pictures Home Entertainment, 2023)
On the brink of losing her childhood home, Maddie discovers an intriguing job listing: wealthy helicopter parents looking for someone to "date" their introverted nineteen-year-old son, Percy, before he leaves for college. To her surprise, Maddie soon discovers the awkward Percy is no sure thing.